Developments in Surrogating Methods - van Dormolen, Hans (LIBER Quarterly: The Journal of the Association of European Research Libraries, 2005)
In this paper, I would like to talk about the developments in surrogating methods for preservation. My main focus will be on the technical aspects of preservation surrogates. This means that I will tell you something about my job as Quality Manager Microfilming for the Netherlands’ national preservation program, Metamorfoze, which is coordinated by the National Library. I am responsible for the quality of the preservation microfilms, which are produced for Metamorfoze. Firstly, I will elaborate on developments in preservation methods in relation to the following subjects: · Preservation microfilms · Scanning of preservation microfilms · Preservation scanning · Computer Output Microfilm. In the closing paragraphs of this paper, I would like to tell you something about the methylene blue test. This is an important test for long-term storage of preservation microfilms. Also, I will give you a brief report on the Cellulose Acetate Microfilm Conference that was held in the British Library in London, May 2005.